Evaluating the impact of market structure in mobile telecommunications markets: panel data analysis for emerging economies - Mutinda, Stanley (School of Economics, 2017)
The mobile telecommunications industry continues to be at the epicentre for growth, innovation, and disruption for virtually all other industries. It is one of the keys to sustainable economic development especially in developing and emerging economies. Over the past two decades, the industry has been very dynamic, experiencing high growth rates. This paper uses econometric models to investigate the impact of market structure on market outcomes such as mobile prices and investment in emerging economies. This is done using quarterly panel data on fifteen emerging economies across four continents for the period between 2006 and 2015. The Herfindahl-Hirschman index (HHI) and the number of operators are used to proxy market structure and effective price per minute paid by consumers and capital expenditure per subscriber are used to proxy mobile prices and investment respectively. Empirical results indicate that increase in market concentration increases market prices. Results also indicate an inverted-U relationship between market concentration and investment. These results indicate that there is a trade-off between static and dynamic efficiency which means that competition in mobile telecommunications reduces both market prices and investments.